Relationship satisfaction in Black couples: the role of self-compassion and openness - Williams, Zenova Nicole (Kansas State University, 2019)
The study explored how Black couples cope with perceived discrimination. More specifically, the study examined how perceived racial discrimination interacted with the enduring strength of self-compassion, and put a strain on couples' relationship processes that have implications for relationship satisfaction. Further, the role of open communication as a potential moderator of the consequences of maladaptive communication patterns on relationship satisfaction was examined. Participants were 210 Black married couples residing in the United States. A common-fate moderated mediation model was used to analyze the data. The results indicated that first, for both spouses, the higher the self-compassion, the lower was couple negative interactions. Second, for wives, self-compassion’s relationship with negative interaction changed when discrimination perceived was high. Third, couple negative interaction was found to suppress the positive effects of self-compassion on relationship satisfaction. Fourth, for wives, openness changed the relationship between negative interaction and relationship satisfaction. Fifth, conditional indirect effects were found only for wives -- the extent self-compassion was related to relationship satisfaction through negative interaction was dependent on both the amount of discrimination perceived by wives and the degree of open communication wives reported in their relationships. The findings have implications for clinical work as well as further research.
Keywords: Black couples; Relationship satisfaction; Discrimination; Self-compassion; Openness